Different approaches to explore the impact of COVID-19 lockdowns on carbonaceous aerosols at a European rural background site - Mbengue, Saliou; Vodička, Petr; Komínková, Kateřina; Zíková, Naděžda; Schwarz, Jaroslav; Prokeš, Roman; Suchánková, Lenka; Julaha, Kajal; Ondráček, Jakub; Holoubek, Ivan; Ždímal, Vladimír (The Science of the total environment, 2023)
To prevent the fast spread of COVID-19, worldwide restrictions have been put in place, leading to a reduction in emissions from most anthropogenic sources. In this study, the impact of COVID-19 lockdowns on elemental (EC) and organic (OC) carbon was explored at a European rural background site combining different approaches: - "Horizontal approach (HA)" consists of comparing concentrations of pollutants measured at 4 m a.g.l. during pre-COVID period (2017-2019) to those measured during COVID period (2020-2021); - "Vertical approach (VA)" consists of inspecting the relationship between OC and EC measured at 4 m and those on top (230 m) of a 250 m-tall tower in Czech Republic. The HA showed that the lockdowns did not systematically result in lower concentrations of both carbonaceous fractions unlike NO2 (25 to 36 % lower) and SO2 (10 to 45 % lower). EC was generally lower during the lockdowns (up to 35 %), likely attributed to the traffic restrictions whereas increased OC (up to 50 %) could be attributed to enhanced emissions from the domestic heating and biomass burning during this stay-home period, but also to the enhanced concentration of SOC (up to 98 %). EC and OC were generally higher at 4 m suggesting a greater influence of local sources near the surface. Interestingly, the VA revealed a significantly enhanced correlation between EC and OC measured at 4 m and those at 230 m (R values up to 0.88 and 0.70 during lockdown 1 and 2, respectively), suggesting a stronger influence of aged and long distance transported aerosols during the lockdowns. This study reveals that lockdowns did not necessarily affect aerosol absolute concentrations but it certainly influenced their vertical distribution. Therefore, analyzing the vertical distribution can allow a better characterization of aerosol properties and sources at rural background sites, especially during a period of significantly reduced human activities.
Keywords: Čína; senioři; Seasons; Rural background site; pevné částice; monitorování životního prostředí; látky znečišťující vzduch; kontrola infekčních nemocí; Air Pollutants; uhlík; Atmospheric aerosols; Environmental Monitoring; COVID-19; China; Temporal variation; Respiratory Aerosols and Droplets; Carbon; Communicable Disease Control; respirační aerosoly a kapénky; COVID-19 lockdowns; Organic - elemental carbon; Humans; Particulate Matter; Vertical distribution; Aged; roční období; lidé